2019
DOI: 10.1002/ep.13296
|View full text |Cite
|
Sign up to set email alerts
|

On the wind blade's surface roughness due to dust accumulation and its impact on the wind turbine's performance: A heuristic QBlade‐based modeling assessment

Abstract: The development of wind projects requires good knowledge of energy production that depends on the rotor aerodynamics and its potential of making optimal use of wind power. It has been noted that dust accumulation across the rotor's blade surfaces can seriously affect the overall wind farm (WF) performance and lead to severe energy losses. In the present work, surface roughness that occurs on the wind blade surfaces due to dust accumulation and its possible effect on wind turbine's performance, are the subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…If the partnership between U-I is successfully established and stable regarding knowledge-transfer and coordination, both participants can benefit in various sectors. The data from academia can be utilised to build new ideas (Xydis, Pechlivanoglou, & Nayeri, 2015), proof of concepts (Papadopoulou, Alasis, & Xydis, 2019), and eventually products (Koscis & Xydis, 2019). According to Lee (2000), each participant must fulfil the requirements and needs of the other in order to maintain this profitable collaboration and both of them achieve their goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the partnership between U-I is successfully established and stable regarding knowledge-transfer and coordination, both participants can benefit in various sectors. The data from academia can be utilised to build new ideas (Xydis, Pechlivanoglou, & Nayeri, 2015), proof of concepts (Papadopoulou, Alasis, & Xydis, 2019), and eventually products (Koscis & Xydis, 2019). According to Lee (2000), each participant must fulfil the requirements and needs of the other in order to maintain this profitable collaboration and both of them achieve their goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jung and Baeder (2020) studied the effects of the surface roughness of the NERL Phase VI wind turbine blades on the airflow characteristics. Papadopoulou et al (2020) investigated the accumulation of dust of wind turbine blades in different areas. They found that the accumulation of dust caused power dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Corsini et al 18 found that at the same operating point and power output, different blade geometries lead to different local flow fields, leading to completely different forms of erosion on wind turbines. Also, Papadopoulou 19 studied the influence of sand particles on the aerodynamic performance of wind turbines, and Fan 20 studied the influence of volume fraction and particle diameter on the torque characteristics of wind turbines using numerical simulation methods. The results showed that the torque of wind turbines in a sand-wind flow is greater than that in a clean airflow in the wind speed range of 3 to 17 m/s, indicating that sand-wind flow can increase the power output of wind turbines.…”
Section: Introductionmentioning
confidence: 99%